Oral health awareness in school-going children and its significance to parent's education level - Apurva Mishra; Ramesh Kumar Pandey; Heena Chopra; Varuni Arora (Wolters Kluwer Medknow Publications, 2018)
Background: The oral health imparts a major impact on one's quality of life. Since last decades, there is an increase in the prevalence of dental afflictions which can be avoided by the knowledge of simple preventive measures. Aim: The aim of this study was to assess the oral health status of children and to analyze its association with the education level of their parents. Materials and Methods: Two randomly schools were selected and all the children from 5-15 years willing to participate in the present cross-sectional study were assessed for oral health status using the World Health Organization for the oral health awareness in children, 2004. Both child and parents were directly interviewed to avoid any bias in understanding the questionnaire. Statistical Package for the Social Sciences (16.0) was used for data analysis. Chi-square/Fisher's exact test was used to compare the dichotomous variables. Results: A total of 210 (133 males and 77 females) children were assessed along with their parents for the awareness of child's oral health condition. Totally 134 (63.3%) children were of age group 5-10 years, while 76 (36.7%) children were of age group 11-15 years. Children with uneducated parents have often experienced toothache, brushes once a daily and frequently visits the dentist for toothache compared to children of educated parents, and this association was observed to be statistically significant (<0.001). Conclusion: The oral health status of children was average. However, education level and awareness of parents regarding oral health preventive measures play a key role in determining the oral health of children.